(untitled) (Development Service Industry Management, 2024)
Tourism is a multifaceted phenomenon that encompasses various types of activities and has a significant impact on the economy, integrating various sectors of tangible and intangible production. The aim of the article is to improve the classification of tourism by analyzing the relationship between tourism and sectors of the economy (types of economic activity), determining the directions of their interaction and identifying the main types of tourism by purpose, which are formed on the basis of these relationships. The article examines the approaches of scientists to the classification of tourism according to various criteria, which allowed them to be combined into groups, such as socio-economic and legal criteria; organization of tourist travel and the method of providing tourist services; logistics, infrastructure and geographical criteria and time criteria. The division of economic activities into tangible and intangible production is presented. It is substantiated that the absence of a separate section for the designation of tourism indicates that tourism is an interdisciplinary field that includes transport services, entertainment, recreation, culture, temporary accommodation, catering, etc. The sections of the Classifier of Economic Activities (NACE Rev.2) that most fully represent tourism are presented. The article examines the inter-sectoral nature of tourism through the prism of its interaction with types of economic activity according to NACE Rev.2. The assignment of a particular type of tourism to a particular industry is determined depending on the contribution of this industry to the development of tourism or the greatest interaction with the corresponding type of tourism. The main areas of tourism’s relationships with sections of NACE Rev.2 are highlighted. A detailed classification of tourism types by the tourist travel purpose according to the economic sectors (types of economic activity) is proposed, which allows a more accurate assessment of the role of tourism in the economy. The results obtained contribute to a deeper understanding of tourism as an inter-sectoral category and the formation of an effective strategy for managing its development. The results obtained can be used by government agencies, business and scientists to ensure sustainable development of tourism.